Research Patterns on Critical Thinking Skills in Indonesian Language and Literature Journals in PPJB-SIP - Abda’u, Muhammad Fishal Putra; Setiawan, Arif; Musaffak; Yunisa Oktavia (Jurnal Multidisiplin Madani, 2023)
This research is aimed to describe (1) types of research (2) types of quantitative research that is used to analyze critical thinking skills, (3) research subjects that is used by the researchers to examine critical thinking skills, (4) data collection instruments that is used by the researchers to determine critical thinking skills, (5) data analysis methods that is used by the researchers researchers to determine critical thinking skills, and (6) research profiles of critical thinking skills from year to year. The research used content analysis. The data obtained in this research were 26 articles written in journals incorporated in the PPJB-SIP website and database, so that the data in this research were the result of content analysis of research articles on critical thinking skills. The instrument used in this research was content analysis guidelines. The results showed that (1) the dominant type of research used by the researcher was quantitative research, (2) the experimental research design was the most dominant research design used, (3) the research subjects used were dominated by students, (4) the test instrument was the most frequently used instrument to investigate critical thinking skills, (5) the more dominant data analysis method was the t-test, and (6) the research on critical thinking skills was conducted from 2010-2021 with the highest results in year 2019. Finally, this research will be useful in providing valuable information about patterns of critical thinking skills, as well as the basis for familiarizing critical thinking skills in the information age and digital technology